Improving Student Experience in an Introductory Programming Course with an Interactive Textbook - Cooper, Gina; Sullivan, William Shane (2023 IEEE World Engineering Education Conference (EDUNINE), 2023)
There are learning barriers with traditional textbooks, students often do not read the textbook, the contents are outdated, or the cost is exorbitant. There is a need for modern knowledge sources to replace the traditional textbook to engage learners and develop deeper levels of cognition and knowledge retention. This paper introduces zyBooks in a beginning programming course. The course was previously designed to utilize the Python language with activities in an Integrated Development Environment (IDLE). The new design utilizes zyBooks focusing on initial programming concepts. In the design, students use Python to program a data analytics project in a Project-Based Learning (PBL) framework and zyBooks to learn basic programming skills through practical application. The utilization of zyBooks as a modernized source of knowledge resulted in increased achievement of student outcomes and increased student satisfaction with the learning methodology.